Modern concept of a new group of retinal vasculitis - I. A. Loskutov; A. A. Kovrizhkina; O. M. Andryuhina (Российский офтальмологический журнал, 2022)
Retinal vasculitis is a rare condition that occurs both in systemic severe diseases and as an adverse event of intraocular drug injections. With the emergence of new anti-VEGF drugs, a number of international authors report on the occurrence of retinal occlusive vasculitis, which led to a decrease in visual acuity. The review presents possible pathogeneses of this condition, approaches to its diagnosis and an algorithm for managing the patients with occlusive vasculitis.